Charged Pesticide Spray Swath and Volumetric Droplets Distribution Impact by Nozzle Types, Spacing and Height: Pesticide Spray Distribution and Nozzle Effects (Journal of Science and Technology, 2025)
Understanding charged pesticide spray swath and volumetric droplets distribution in a spray continuum is an innovative strategy to reduce spray overlap and improve spraying efficiency. Pesticides spray overlap and accumulation on substrates from single or multiple nozzle(s) do not only waste chemicals but also increase lethal dosage. The parameters to enhance uniformity of in-situ droplet deposition at reduced surface overdose are required for efficient pesticide application. A factorial experiment arranged in a Completely Randomised Design comprising flat-fan (FF) and hollow-cone (HC) nozzle types, 2, 3, 4 bar flow pressures, 50, 75, 100 and 120 cm nozzle spacings (S) and 40, 50, 60 cm spraying heights (H) at three replicates were investigated to determine charged spray swath (Wn) and volumetric (Qn ) droplets distribution from a developed inductive nozzle cap mounted on a telescopic boom. The FF-nozzle produced relatively smaller charged droplet sizes, DV0.5 (67.4-79.2μm), wider spray swath Wn (R2 = 98.37 %; max. 185 cm) and higher Qn distribution (C37 collectors, 15.86 mls-1), than HC-nozzle of DV0.5 (70-92.5 μm), narrow spray swath Wn (R2 = 85.45 %; max. 115 cm) and lower Qn distribution (C23 collectors, 15.72 mls-1) respectively. A spray Uniformity Index (UI) allowed permissible spraying of FF-nozzles at 0.4 and HC-nozzles at 0.3-0.42, but spraying above 0.33 increased overlap and application rate, and below 0.08 decreased spraying efficiency. Hitherto, spraying from FF-nozzles at 0.12-0.18 yielded uniformity of Qn distribution, while HC-nozzles were effective at 0.25, corresponding to 25-50 % spray overlap. Therefore, to reduce pesticide spray overlap on substrates, FF-nozzles should be mounted at 50 cm H × 100 cm S or HC-nozzles at 60 cm H × 75 cm S on the boom under 4 bar flow pressure, as the electrostatic spraying system provides timely and effective pesticide application in crop protection.